Policy Adoption of the Travel Bubble in Increasing Tourism in Bintan Regency, Riau Islands Province - Chaerey Ranba Sholeh; Adhityo Nugraha Barsei; Alan Nuari; Firman Firman (Universitas Padjadjaran, 2022)
Tourism is one of the leading sectors that makes a huge contribution, especially in the Riau Islands. However, with the Covid-19 pandemic, the number of tourists visiting the Riau Islands dropped significantly, so the government needed to innovate by adopting a travel bubble policy. The purpose of this study was to see how the process of adopting the travel bubble policy in reactivation of the economy and tourism in Bintan Regency, especially during the Covid-19 pandemic. The research method used is qualitative with a descriptive approach. The results of this study are from several stages in the policy adoption process, namely the knowledge stage, persuasion stage, decision stage, implementation stage, and confirmation stage of the application of the travel bubble that has not been fully implemented properly and effectively by the government. This study suggests the need for an adoption process in implementing policy innovations, namely the need for knowledge and fast decision-making in the adoption process so that tourism in the Riau Islands is not disturbed by the pandemic. This study has limitations in obtaining data because the travel bubble policy has just been implemented, so further research can continue the policy implementation process.